Cyclic performance of novel composite beam-to-column connections with reduced beam section fuse elements. (April 2023) - Yao, Yifan; Zhou, Liqi; Huang, Hua; Chen, Zhen; Ye, Yanxia
Abstract: Reduced beam section steel-novel composite frame beam (RSCFB) is described in this study, which is a novel prefabricated composite frame beam. The design of the RSCFB was based on the idea of the post-earthquake resilience and damage control. To this end, two RSCFB specimens and one control specimen were tested to investigate their hysteretic behavior. The experimental results indicated that earthquake resistant behavior of the frame-beam was similar to that of the common steel beam, which all possessed excellent seismic capacity. The application of reduced beam section (RBS) could reduce the length and the steel consumption of cantilever beam. Meanwhile, it improved the service length of composite beam and more steel could be replaced by concrete. Compared to the steel frame beam, the application of the hollow core partially encased composite beam (HPEC beam) in RSCFB-1 not only met requirements of the seismic capacity, but also reduced the steel consumption without increasing the dead weight significantly. The results of experiment were confirmed by finite element models and models were established for a parametric analysis. Based on the results of experiment and finite element parameter analysis, simplified calculation and seismic design requirements are proposed.